Sales Expansion Strategies for S.C. Minimal A.P: A Sustainable Business Growth Approach - BUZOIANU, Ovidiu Andrei Cristian; MEGA, Loredana Nicoletta; PETRESCU, Irina Elena; IACOB (PÂRGARU), Oana Camelia (European Journal of Sustainable Development, 2025)
One of the most critical aspects of this paper is identifying the key factors that determine the success of a sales expansion strategy. These factors include analyzing the market and competition, developing an effective marketing plan, and identifying customer needs. The paper will also examine the various sales channels available to the company, including direct sales, online sales, and partner sales. The advantages and disadvantages of each channel will be evaluated, along with strategies for integrating them into the overall sales expansion plan. Another essential component of this study is assessing how technology can support a company’s sales growth efforts. The analysis will consider technological solutions that enhance the efficiency and productivity of the sales process, as well as their potential to improve the overall purchasing experience for customers. Finally, this paper will present an overview of the different approaches to increasing a company’s sales, offering a detailed analysis of the advantages and disadvantages of each method and how these can be effectively implemented in the specific context of S.C. MINIMAL A.P. Keywords: development, resources, sales, supply